Características produtivas, morfogênicas e estruturais do capim Piatã submetido à adubação orgânica - Orrico Júnior, Marco Antonio Previdelli; Centurion, Stanley Ribeiro; Orrico, Ana Carolina Amorim; Oliveira, Arley Borges de Morais; Sunada, Natália da Silva [UNESP] (Universidade Federal de Santa Maria, 2013)
The organic fertilizer can be a viable alternative in the production of forage grasses, however there is little information regarding doses and composition of the major organic fertilizers. The aim of this paper was to verify the influence of the different doses of organic compost produced from two types of poultry litter on the structural, morphogenetic and productive characteristics of Brachiaria brizantha cv 'Piatã'. The experiment was conducted in a greenhouse in a completely randomized design in a factorial scheme l with parcel subdivided in time. The parcels were composed by six treatments: two types of compost (poultry litter based in sugar cane and napier grass) in three doses (100, 200 and 300kg ha-1 equivalent N.) and the subparcels by the four different periods of cut. The composts were applied in a unique dose, after the uniformization cut, at the quantities: 11,36 and 11,83, 22,73 and 23,67, 34,09 and 35,50 g pot-1 for the poultry litter based in sugar cane and napier grass, respectively which are equivalent to the rates of 0, 100, 200 and 300kg ha-1 of N. The variables measured were: dry matter production (DMP), leaf appearance rate (LApR), phyllochron, leaf elongation dose (LER) and shoots elongation rate (SER), number of green leaves (NGL), final size of the leaf (FSL). No significant difference between the types of composts and in the interaction compost x doses was observed, thus, both could be used without the risk of loss in the use of the nutrients by the plants evaluated in the experiment. There was a significant difference between the DMP, LApR, phyllochron, LER, SER, NGL and FSL because of the increasing rates of nitrogen, followed by a linear model of prediction. The effect of the periods of slaughter was also observed, where the slaughters carried out in the summer presented a better performance over the morphogenetic and structural features evaluated.

A adubação orgânica pode ser uma alternativa viável na produção de gramíneas forrageiras, no entanto poucas são as informações referentes às doses e à composição dos principais adubos orgânicos. O objetivo do trabalho foi verificar a influência das diferentes doses de composto orgânico produzido com dois tipos de cama de frango sobre as características produtivas, morfogênicas e estruturais de Brachiaria brizantha, cv 'Piatã'. O experimento foi conduzido em casa de vegetação em delineamento inteiramente casualizado, em esquema fatorial com parcela subdividida no tempo. As parcelas foram compostas por seis tratamentos: dois tipos compostos (cama de frango a base de cana de açúcar ou napier) em três doses (100, 200 e 300kg ha-1 equivalente N) e as subparcelas pelos quatro períodos de cortes. Os compostos foram aplicados em dose única, após o corte de uniformização, nas quantidades de: 11,36 e 11,83, 22,73 e 23,67, 34,09 e 35,50g vaso-1 para os compostos de cama de frangos a base de cana de açúcar e capim napier, respectivamente, que equivalem às doses de 100, 200 e 300kg ha-1 de N. As variáveis mensuradas foram: produção de matéria seca (PMS), taxa de aparecimento de folha (TApF), taxa de alongamento de folha (TAlF), filocrono, taxa de alongamento de pseudocolmo (TAlC), comprimento final de folha (CFF) e números de folhas verdes (NFV). Não foi observada diferença significativa entre os tipos de composto e na interação composto x dose. Dessa forma, ambos poderiam ser utilizados sem que ocorresse prejuízo no aproveitamento dos nutrientes pelas plantas avaliadas no experimento. Houve diferença significativa entre a PMS, TApF, filocrono, TAlF e TAlC, NFV e TFF em função das doses crescentes de nitrogênio, segundo um modelo linear de predição. Também foi observado efeito dos períodos de corte, em que os cortes realizados no verão apresentaram melhor desempenho sobre as características morfogênicas e estruturais.
Structural, morphogenetic and productive features of Piatã Grass subjected to organic fertilization
Keywords: Brachiaria brizantha; filocrono; matéria seca; nitrogênio; Brachiaria brizantha; phyllochron; dry matter; nitrogen